Benign Mixed Mammary Tumour with Hepatoid Gland Differentiation in a Dog. (September 2022) - Otsuka, Narumi; Hirata, Akihiro; Yonemaru, Kayoko; Goto, Minami; Murakami, Mami; Sakai, Hiroki
Summary: A 10-year-old spayed female Shih Tzu underwent surgery to remove a tumour (8 mm diameter) in the right 4 th mammary gland. Histopathologically, the tumour consisted of four different components: luminal epithelial cells, myoepithelial cells, cartilage and well-differentiated hepatoid gland-like cells. There were multiple nests composed predominantly of hepatoid gland-like tissue with a small number of tubules formed by luminal epithelial cells at the periphery, in which continuity between the two components was seen. Immunolabelling for cytokeratins (CK14, CK18 and CK19), p63 and α-smooth muscle actin clearly distinguished the neoplastic luminal epithelial, myoepithelial and hepatoid gland-like cells. The immunohistochemical phenotype of the hepatoid gland-like neoplastic cells was identical to that of normal hepatoid gland cells. Based on these findings, a diagnosis of benign mixed tumour of the mammary gland with differentiated hepatoid gland cells was made. To our knowledge, this is the first report of a canine mammary tumour with hepatoid gland differentiation. Graphical abstract: Image 1